Soil fauna abundance under birch and willow vegetation in girdled and non-girdled plots, subarctic Sweden, 2019 ... - Parker, T.C.; Chomel, M.; Clemmensen, K.E.; Friggens, N.L.; Hartley, I.P.; Johnson, D.; Krab, E.J.; Lindahl, B.D.; Street, L.E.; Subke, J.A.; Wookey, P.A. (NERC EDS Environmental Information Data Centre, 2022)
Data comprise numbers of soil microarthorpods (mesofauna) extracted over 10 days from soils in northern, subarctic Sweden sampled on 29th July 2019. Soils were sampled from treeline mountain birch forest and stands of tundra willow that were wither 'girdled' (connection between leaves and roots cut by disrupting the phloem transport) or ‘control’ (no treatment), two years prior. ... : Soils were sampled across all plots for microarthropods (Collembola and mites) on July 29th 2019. Within each plot, three 4.5 cm diameter soil cores were taken to the depth of the soil horizon (until rock or last clasts) within the central 3 x 3 m area of the birch plots, and across the willow plots. The mineral horizon of each soil core was removed and discarded, while the litter horizon was retained and pooled separately for each plot. Cores were inserted into tight fitting plastic rings to maintain soil structure for optimal extraction efficiency. The soil and litter samples were extracted for soil fauna using a Tullgren Funnel fauna extractor. 22 pooled soil and 22 pooled litter samples were placed at random under individual heat lamps (in order to avoid spatial biases in extraction efficiency) and left for 10 days to extract fauna into ethanol. At the end of the extraction the soil and litter samples were oven dried for 24 hours at 70 °C and weighed to determine soil dry weights. The fauna samples were ...